Effect of ZnS nanoparticles on the photoluminescence of Sm3+ ions in methanol. (October 2016) - Kakoti, D; Rajkonwar, N; Dehingia, N; Boruah, A; Gogoi, P; Dutta, P
Abstract: ZnS nanoparticles co-doped with Sm 3+ ions were prepared in methanol medium for fixed Sm 3+ and varying ZnS concentrations. Enhancements in absorption as well as photoluminescence efficiency of the co-doped samples were observed. This enhanced efficiency is attributed to the effective increase in oscillator strengths of the Sm 3+ transitions because of the addition of ZnS nanoparticles.